New English File : Elementary. Teacher's book - Oxenden, Clive; Latham-Koenig, Christina; Seligson, Paul.; Byrne, Tracy (Oxford : Oxford University Press, cop., 2004)
Containing ideas and photocopiables, this book helps students by providing them with a student package including Workbook, MultiROM, and website, all working together and cross-referenced by a study link
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Spoken English; English language -- Study and teaching (Secondary)